New Trends in Industrial Automation - Li, Pengzhong (IntechOpen, 2019)
New technological developments expand the technical connotation of industrial automation with control objects and control objectives also greatly expanded, thus promoting development direction of industrial automation technology to intellectualization. This book is a collection of articles on novel approaches to current problems in industrial automation and encompasses multidisciplinary areas such as distributed system architecture, application of non-destructive distributed sensor system, joint simulation technology, and a summary of intelligent transition. New Trends in Industrial Automation provides useful reference material for technical workers in the field of industrial automation, including undergraduate and postgraduate students, academicians, researchers, and practicing engineers.